Characterization of latent heat storage system of MEPCM-incorporated paint - Sabarillo, Noel S. (College of Engineering, University of the Philippines Diliman, 2014)
Determining the effect of the homogenization speed and pre-polymer dropping rate during synthesis of microencapsulated phase change materials (MEPCMs) and concentration of MEPCMs in paint on the temperature buffering capacity of the latent heat storage system (LHS) of MEPCM-incorporated paints is the primary objective of this study. MEPCMs with n-octadecane as core and resorcinol-modified urea-melamine-formaldehyde (UMF) as polymer shell were synthesized at homogenization speeds of 4500rpm and 1000rpm. For each speed, four different pre-polymer dropping rates were employed a) max - all at once, b) 1 drop for every second - 3mL/min c) 1 drop for every three seconds - 1mL/min and d) 1 drop for every 5 seconds - 0.6mL/min. FTIR characterization confirmed the success of microencapsulation. SEM revealed that increasing the homogenization speed and decreasing the pre-polymer dropping rate decreases the size and increase the sphericity of the microcapsules. DSC results showed that latent heat and encapsulation ratio increases with increasing homogenization speed and decreasing pre-polymer dropping rate. The synthesized and characterized MEPCMs were incorporated to paint in 10%, 5% and 1% concentrations. For the set of conditions employed, temperature profiling exposed that the temperature buffering capacity of the LHS system generally increases with increasing homogenization speed (1000rpm to 4500rpm), decreasing pre-polymer dropping rate (3mL/min to 0.6mL/min) and increasing MEPCM concentration (1% to 10%).